2020
DOI: 10.1161/circulationaha.120.050304
|View full text |Cite|
|
Sign up to set email alerts
|

Initial Invasive Versus Conservative Management of Stable Ischemic Heart Disease in Patients With a History of Heart Failure or Left Ventricular Dysfunction

Abstract: Background: It is unknown whether an initial invasive strategy in patients with stable ischemic heart disease and at least moderate ischemia improves outcomes in patients with a history of heart failure (HF) or left ventricular dysfunction (LVD) when EF ≥35%, but <45%. Methods: Among 5179 participants randomized into the International Study of Comparative Health Effectiveness with Medical and Invasive Approaches (ISCHEMIA), all of whom had LVEF ≥35%,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
73
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(83 citation statements)
references
References 28 publications
4
73
0
6
Order By: Relevance
“…Indeed, the large majority of patients had LVEF ≥ 50% (median [IQR] = 60 [55–65]%) ( 5 ). Interestingly, a recent ancillary study of ISCHEMIA assessing only the subgroup of patients with LVEF 35–45% suggested a better event-free survival rate after an initial invasive strategy ( 52 ) ( Figure 3 ). However, initial studies assessing the potential interest of coronary revascularization in patients with reduced LVEF did not suggest any benefit in terms of CV outcomes.…”
Section: Subgroups With Specific Benefit Of Revascularisation: Heart Failure Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the large majority of patients had LVEF ≥ 50% (median [IQR] = 60 [55–65]%) ( 5 ). Interestingly, a recent ancillary study of ISCHEMIA assessing only the subgroup of patients with LVEF 35–45% suggested a better event-free survival rate after an initial invasive strategy ( 52 ) ( Figure 3 ). However, initial studies assessing the potential interest of coronary revascularization in patients with reduced LVEF did not suggest any benefit in terms of CV outcomes.…”
Section: Subgroups With Specific Benefit Of Revascularisation: Heart Failure Patientsmentioning
confidence: 99%
“… Cumulative incidence curves for the primary composite outcome according to randomized treatment and history of heart failure (HF) or left ventricular dysfunction (LVD), from ISCHEMIA trial ( 52 ). CON indicates conservative strategy; and INV, invasive strategy.…”
Section: Subgroups With Specific Benefit Of Revascularisation: Heart Failure Patientsmentioning
confidence: 99%
“…Recently, there has been increasing interest in the early revascularization of subgroups of patients with heart failure. In the small, high-risk subgroup in the ISCHEMIA trial with heart failure and LVEF of 35% to 45%, an initial invasive approach was associated with better event-free survival [ 6 ]. However, upon analysis of a pooled database of five nationwide prospective registries from 55 centers in Korea, Kang et al demonstrated that complete revascularization reduced three-year adverse events only in patients with preserved LVEF.…”
Section: Advances In Pci For Stable Ischemic Heart Diseasementioning
confidence: 99%
“…In dieser Subgruppenanalyse der ISCHEMIA-Studie fiel auf, dass bei Patienten mit relevanter myokardialer Ischämie (> 10 % des Myokards) und eingeschränkter linksventrikulärer Funktion eine frühe Revaskularisation im Vergleich zu einer alleinigen OMT zu einer Verbesserung der Prognose führte [25] In der bereits 2016 vorgestellten STICH-Studie wurde gezeigt, dass Patienten mit ischämischer Kardiomyopathie (HFrEF mit EF < 35 %) und relevanter KHK von einer Bypassoperation (ACB) im Vergleich zu einer alleinigen optimalen medikamentösen Therapie profitieren [26]. Während einer Nachbeobachtung von 9,8 Jahren wurde die Mortalität signifikant nach ACB reduziert (58,9 % vs. 66,1 % bei alleiniger medikamentöser Therapie; HR: 0,84; 95 %-KI 0,73-0,97; p = 0,02).…”
Section: Revaskularisation Bei Hfrefunclassified